THE EXILE AND DEATH OF FLAVIAN OF CONSTANTINOPLE: A PROLOGUE TO THE COUNCIL OF CHALCEDON - Chadwick, Henry (The journal of theological studies, 1955)
H. CHADWICK; THE EXILE AND DEATH OF FLAVIAN OF CONSTANTINOPLE: A PROLOGUE TO THE COUNCIL OF CHALCEDON, The Journal of Theological Studies, Volume VI, Issue 1, 1